Characterization of a Novel PolyM-Preferred Alginate Lyase from Marine Vibrio splendidus OU02 - Zhuang, Jingjing (Mar Drugs, 2018)
Alginate lyases are enzymes that degrade alginate into oligosaccharides which possess a variety of biological activities. Discovering and characterizing novel alginate lyases has great significance for industrial and medical applications. In this study, we reported a novel alginate lyase, AlyA-OU02, derived from the marine Vibrio splendidus OU02. The BLASTP searches showed that AlyA-OU02 belonged to polysaccharide lyase family 7 (PL7) and contained two consecutive PL7 domains, which was rare among the alginate lyases in PL7 family. Both the two domains, AlyA(a) and AlyA(b), had lyase activities, while AlyA(a) exhibited polyM preference, and AlyA(b) was polyG-preferred. In addition, the enzyme activity of AlyA(a) was much higher than AlyA(b) at 25 °C. The full-length enzyme of AlyA-OU02 showed polyM preference, which was the same as AlyA(a). AlyA(a) degraded alginate into di-, tri-, and tetra-alginate oligosaccharides, while AlyA(b) degraded alginate into tri-, tetra-, and penta-alginate oligosaccharides. The degraded products of AlyA-OU02 were similar to AlyA(a). Our work provided a potential candidate in the application of alginate oligosaccharide production and the characterization of the two domains might provide insights into the use of alginate of this organism.